2021
DOI: 10.1002/chem.202102442
|View full text |Cite
|
Sign up to set email alerts
|

A Full Flexible NH4+ Ion Battery Based on the Concentrated Hydrogel Electrolyte for Enhanced Performance

Abstract: Non-metal ammonium (NH þ 4 ) ions have recently been explored as effective charge carriers in battery systems due to their abundancy, light weight, small hydration shells in water. The research concerning the use of NH þ 4 redox chemistry in batteries, particularly in flexible batteries, is still in its infancy. For the first time, we report a flexible full NH þ 4 ion battery (AIB) composed of a concentrated hydrogel electrolyte sandwiched between NH 4 V 3 O 8 • 2.9H 2 O nanobelts cathode and polyaniline (PANI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…60 In the other report, Kuchena and Wang presented a fully flexible AIB using a concentrated hydrogel electrolyte sandwiched between an ammonium vanadate cathode and a polyaniline anode. 61 The concentrated hydrogel electrolyte was synthesized by simply mixing (NH 4 ) 2 SO 4 , xanthan gum, and water, as shown in Figure 7 b,c. By varying the amount of salt in the electrolyte (prepared using 1, 2, or 3 m solution), it was found that the battery composed of the gel electrolyte prepared from the 3 m salt solution delivers the best initial capacity of 55 mA g –1 as well as good cyclability over 250 cycles at 0.1 A g –1 , as this electrolyte has the highest ionic conductivity of 6.1 × 10 –3 S cm –1 and the largest tensile strength of 4.36 kPa among the three.…”
Section: Electrolytes For Ammonium-ion Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…60 In the other report, Kuchena and Wang presented a fully flexible AIB using a concentrated hydrogel electrolyte sandwiched between an ammonium vanadate cathode and a polyaniline anode. 61 The concentrated hydrogel electrolyte was synthesized by simply mixing (NH 4 ) 2 SO 4 , xanthan gum, and water, as shown in Figure 7 b,c. By varying the amount of salt in the electrolyte (prepared using 1, 2, or 3 m solution), it was found that the battery composed of the gel electrolyte prepared from the 3 m salt solution delivers the best initial capacity of 55 mA g –1 as well as good cyclability over 250 cycles at 0.1 A g –1 , as this electrolyte has the highest ionic conductivity of 6.1 × 10 –3 S cm –1 and the largest tensile strength of 4.36 kPa among the three.…”
Section: Electrolytes For Ammonium-ion Batteriesmentioning
confidence: 99%
“…(f) Photo showing the flexible battery lighting up LED light bulbs. Panels (d,e) are reproduced with permission from ref ( 61 ). Copyright 2021 Wiley.…”
Section: Diverse Applications Of Ammonium-ion Storagementioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8] Consequently, lots of framework materials have been explored extensively and some of them are identified as electroactive materials for ammonium ion batteries, e.g. transition metal oxides, [9][10][11][12] organic compounds, [13][14][15] and metal organic frameworks. 2,16 Among the multitudinous reported compounds, Prussian blue analogues as a member of metal organic frameworks are regarded as conceivable cathode can-didates, partly because of their low cost, eco-friendliness, and easy accessibility.…”
Section: Introductionmentioning
confidence: 99%